Diabetes mellitus increases the risk of post-COVID-19 pulmonary fibrosis: a meta-analysis of observational studies - Fen Tan; Chenyu Li; Jingyi Hu; Shanshan Liu; Weijun Peng; Hong Peng; Can Hou; Chao Wu; Zhiguang Zhou; Yang Xiao (BMC Pulmonary Medicine)
Abstract Background Pulmonary fibrosis (PF) is a serious respiratory complication observed in coronavirus disease 2019 (COVID-19) patients, and people with diabetes mellitus (DM) are at an increased risk of developing severe COVID-19. However, whether DM is a risk factor for post-COVID-19 pulmonary fibrosis (PCPF) remains unknown. Methods We conducted a meta-analysis of observational studies to evaluate the association between DM and the development of PCPF. We searched PubMed, EMBASE, and the Cochrane Library for relevant studies published before February 1, 2023, without language or publication type restrictions. We calculated odds ratio (OR) with 95% confidence interval (CI) to compare the prevalence of DM among COVID-19 patients with PCPF with that among non-PCPF controls. Results This meta-analysis included a total of 5,088 COVID-19 patients. We found a significant association between DM and the development of PCPF (OR = 2.18, 95% CI: 1.15–4.13, P < 0.001), with high heterogeneity among the studies (I2 = 82.2%). Subgroup analysis showed that the association between DM and PCPF was consistent across different geographic regions, study designs, sample sizes, mean ages, DM types, assessment times after COVID-19 onset, and NOS quality ratings. Conclusions This meta-analysis offers evidence supporting a correlation between DM and the development of PCPF among COVID-19 patients. Despite the considerable heterogeneity in this studies, this research retains significant implications for the clinical management of COVID-19 patients. DM is a potential risk factor for PCPF. It is imperative for clinicians to remain vigilant regarding the development of PCPF in COVID-19 patients who complicated with DM.